IoT-based Hospital Bed - Tsai, Eric Yi Cheng; Chew, Chang Choon; Chessda Uttraphan Eh Kan (Evolution in Electrical and Electronic Engineering, 2024)
In this era of globalisation, smart devices have slowly overcome the traditional version of devices where everything is just on the tip of our fingers. The proposed IoT-based hospital bed aims to bring more convenience to the patients and also the guardians. ESP32 microcontroller is used to connect to the handset through Wi-Fi and then control the bed using a handset. ESP32 will trigger the relays to send the signal to each movement when the handset button is pressed. It allows the patients to control the height of the whole bed as well as the adjacent angle of the head and leg over a handset; the bed can also be controlled by using the default wired remote controller. Both methods can be used simultaneously. By using Blynk, the bed can be controlled in multiple movements at the same time, which is better than the default remote controller. Blynk. Besides that, an emergency call button is provided at the interface of Blynk in the handset, where the patient can seek a guardian’s help simply by pressing it. An e-mail will be sent to that guardian when the button is pressed. The bed is then tested, and it is verified that it can be operated as expected using the handset.